Multiple interactions recruit MLL1 and MLL1 fusion proteins to the HOXA9 locus in leukemogenesis. - Milne, T; Kim, J; Wang, G; Stadler, S; Basrur, V; Whitcomb, S; Wang, Z; Ruthenburg, A; Elenitoba-Johnson, K; Roeder, R; Allis, C (2010)
MLL1 fusion proteins activate HoxA9 gene expression and cause aggressive leukemias that respond poorly to treatment, but how they recognize and stably bind to HoxA9 is not clearly understood. In a systematic analysis of MLL1 domain recruitment activity, we identified an essential MLL1 recruitment domain that includes the CXXC domain and PHD fingers and is controlled by direct interactions with the PAF elongation complex and H3K4Me2/3. MLL1 fusion proteins lack the PHD fingers and require prebinding of a wild-type MLL1 complex and CXXC domain recognition of DNA for stable HoxA9 association. Together, these results suggest that specific recruitment of MLL1 requires multiple interactions and is a precondition for stable recruitment of MLL1 fusion proteins to HoxA9 in leukemogenesis. Since wild-type MLL1 and oncogenic MLL1 fusion proteins have overlapping yet distinct recruitment mechanisms, this creates a window of opportunity that could be exploited for the development of targeted therapies.